BioPSTM: a formal model for privacy, security, and trust in template-protecting biometric authentication - Kanak, Alper; Soğukpınar, İbrahim (Wiley-Hindawi, 2014)
[No abstract available]
Keywords: Fuzzy Extractors; Key Generation; Mechanism